Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2006
DOI: 10.1145/1124772.1124812
|View full text |Cite
|
Sign up to set email alerts
|

Fast, flexible filtering with phlat

Abstract: Systems for fast search of personal information are rapidly becoming ubiquitous. Such systems promise to dramatically improve personal information management, yet most are modeled on Web search in which users know very little about the content that they are searching. We describe the design and deployment of a system called Phlat that optimizes search for personal information with an intuitive interface that merges search and browsing through a variety of associative and contextual cues. In addition, Phlat sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
3
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 24 publications
2
96
3
2
Order By: Relevance
“…Desktop search systems such as Stuff I've Seen [9] and Phlat [8] showed that user interaction is a significant issue in the desktop environment, and that date is most important feature since most users sorted the results by date. Other researchers focused more on improving the quality of ranking and proved that temporal locality and causality [18] are useful features.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Desktop search systems such as Stuff I've Seen [9] and Phlat [8] showed that user interaction is a significant issue in the desktop environment, and that date is most important feature since most users sorted the results by date. Other researchers focused more on improving the quality of ranking and proved that temporal locality and causality [18] are useful features.…”
Section: Related Workmentioning
confidence: 99%
“…The criteria that we used for the documents in a desktop were that the documents should be related to a particular person, there should be of a variety of document types, the different document types should have metadata or fields, and that the collection should be of reasonable size, although there is no hard limit on size since real-world desktops vary considerably. [8] The privacy of the target individual was another concern.…”
Section: Collecting Documentsmentioning
confidence: 99%
See 2 more Smart Citations
“…LFAi sb ased on recorded user interactions with aP IM tool, normally in naturalistic conditions out-with the control of the experimenter[ DCC + 03, CRDS06,TAJP07]. LFAe xamines the quantitative aspects of user behaviour,i ncluding the nature of submitted queries and the properties of items accessed.…”
Section: Introductionmentioning
confidence: 99%